Decline of Professional Activity and the Needs Fulfilled by Work. Comparative Analysis of Polish and Czech Working Retirees - Swadźba, Urszula (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
The article aims to investigate how work satisfies values and needs of retired workers through the theoretical concept of active aging. It discusses the three needs that work satisfies (economic, social, and self-realization) and references Ronald Inglehart’s concept of changes in the value system. The results of quantitative research conducted in 2019 in the Czech Republic (Ostrava) and Poland (Katowice), along with qualitative research conducted in 2024, were used for the empirical analysis. The quantitative research aimed to scrutinize the life and work strategies of the 55–65-year-old generation in large cities (169 interviews were conducted in Poland and 152 in the Czech Republic). The qualitative research utilized an in-depth interview (12 in Poland and 10 in the Czech Republic), with the results drawing comparisons between retirees who are still working and the remaining working 55-plus generation. Similarities and differences in the needs and values satisfied by work among the two analyzed groups are then discussed.